Pengembangan e-LKPD Berbasis Realistic Mathematics Education (RME) Berbantuan Google Form untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas IV SD - Asni, Ade Saswita; Hidayat, Wahyu (Medan Resource Center, 2023)
The Covid-19 pandemic forced a swift shift to online learning, prompting the creation of innovative tools like e-Worksheets. This study introduces e-LKPD, a product grounded in Realistic Mathematics Education (RME) and facilitated through Google Forms, designed to enhance critical thinking skills in fourth-grade students. Utilizing the Research and Development (R&D) method with the ADDIE model, the product underwent rigorous evaluation. Results revealed high validity percentages (92.05% for media, 84.67% for material, 94.28% for language) and practicality (93% teacher response, 84.67% student response). Importantly, the e-LKPD demonstrated effectiveness in improving critical thinking skills, establishing itself as a crucial resource for sustaining educational quality amid the challenges posed by the pandemic, ensuring continued progress in the realm of online education. The development of this e-LKPD aligns with the evolving landscape of education, providing a valuable tool to foster critical thinking skills in the digital era.